2007
DOI: 10.1016/j.applanim.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the pet dog: Influence of owner and dog's characteristics

Abstract: The present study investigates how characteristics of both the dog, Canis familiaris, and their owner\ud influence the quality of life (QoL) of the pet dog. The investigation was carried out using a multiple\ud approach: (1) three questionnaires which investigated characteristics of the dog and their owner and\ud care given to the dog, (2) simple physical examination of the dog, (3) the Strange Situation Test to\ud investigate the dog’s attachment to their owner and (4) the Lexington Attachment to Pets Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 46 publications
6
67
1
14
Order By: Relevance
“…This agrees with previous research, in which human factors have been found to have an important effect in dog-owner relationship, experiences and management, such as relinquishment [7], level of attachment to the dog [26, 49], responsible dog ownership practices [19, 26] or level of relationship [18,26]. Ultimately this may indicate that certain aspects of the owner-dog relationship may be a marker of the person’s psychological state and/or the availability of, and individual ability to use, other sources of social support.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with previous research, in which human factors have been found to have an important effect in dog-owner relationship, experiences and management, such as relinquishment [7], level of attachment to the dog [26, 49], responsible dog ownership practices [19, 26] or level of relationship [18,26]. Ultimately this may indicate that certain aspects of the owner-dog relationship may be a marker of the person’s psychological state and/or the availability of, and individual ability to use, other sources of social support.…”
Section: Discussionsupporting
confidence: 92%
“…Most respondents were female (80.66%). This high proportion of females is consistent with previous human-companion animal interaction research (Ley, Bennett, & Coleman, 2008;Marinelli, Adamelli, Normando, & Bono, 2007). The majority of respondents resided in Melbourne's outer suburbs (64.2%), although some respondents lived in inner city Melbourne (18.4%) or on rural properties (12.3%).…”
Section: Methods Participantssupporting
confidence: 86%
“…When dogs socialized with humans were given the choice between interacting with another dog and a human, dogs often preferred social interaction and proximity with the human (Tuber, Sanders, Hennessy, & Miller, 1996). test which type of attachment animals have developed toward their human caregivers (e.g., Marinelli, Adamelli, Normando, & Bono, 2007;Palmer & Custance, 2008;Topal et al, 2005). More re cently, Zilcha-Mano et al (201 la) directly applied Bowlby's psy chological attachment taxonomy and developed the Pet Attach ment Questionnaire, which assesses attachment anxiety and avoidance.…”
Section: Contacts With Animals Across the Life Spanmentioning
confidence: 99%